Circadian Pattern of Ion Channel Gene Expression in Failing Human Hearts. (January 2021) - McTiernan, Charles F.; Lemster, Bonnie H.; Bedi, Kenneth C.; Margulies, Kenneth B.; Moravec, Christine S.; Hsieh, Paishiun Nelson; Shusterman, Vladimir; Saba, Samir
Abstract : Background: Ventricular tachyarrhythmias and sudden cardiac death show a circadian pattern of occurrence in patients with heart failure. In the rodent ventricle, a significant portion of genes, including some ion channels, shows a circadian pattern of expression. However, genes that define electrophysiological properties in failing human heart ventricles have not been examined for a circadian expression pattern. Methods: Ventricular tissue samples were collected from patients at the time of cardiac transplantation. Two sets of samples (n=37 and 46, one set with a greater arrhythmic history) were selected to generate pseudo-time series according to their collection time. A third set (n=27) of samples was acquired from the nonfailing ventricles of brain-dead donors. The expression of 5 known circadian clock genes and 19 additional ion channel genes plausibly important to electrophysiological properties were analyzed by real-time polymerase chain reaction and then analyzed for the percentage of expression variation attributed to a 24-hour circadian pattern. Results: The 5 known circadian clock gene transcripts showed a strong circadian expression pattern. Compared with rodent hearts, the human circadian clock gene transcripts showed a similar temporal order of acrophases but with a ≈7.6 hours phase shift. Five of the ion channel genes also showed strong circadian expression. Comparable studies of circadian clock gene expression in samples recovered from nonheart failure brain-dead donors showed acrophase shifts, or weak or complete loss of circadian rhythmicity, suggesting alterations in circadian gene expression. Conclusions: Ventricular tissue from failing human hearts display a circadian pattern of circadian clock gene expression but phase-shifted relative to rodent hearts. At least 5 ion channels show a circadian expression pattern in the ventricles of failing human hearts, which may underlie a circadian pattern of ventricular tachyarrhythmia/sudden cardiac death. Nonfailing hearts from brain-dead donors show marked differences in circadian clock gene expression patterns, suggesting fundamental deviations from circadian expression. Abstract : Supplemental Digital Content is available in the text.